DNA- and telomere-damage does not limit lifespan: evidence from rapamycin - Blagosklonny, Mikhail V. (Aging (Albany NY), 2021)
Failure of rapamycin to extend lifespan in DNA repair mutant and telomerase-knockout mice, while extending lifespan in normal mice, indicates that neither DNA damage nor telomere shortening limits normal lifespan or causes normal aging.